Evaluation Of Genexpert Performance Assays In Sputum Samples In Cavitary Pulmonary TB/Role Of Genexpert In Diagnosing Pulmonary Tuberculosis - Shafique, Aisha; Arshad, Eishal; Daud, Sara (Journal of Rawalpindi Medical College, 2025)
Objective: This study evaluated the diagnostic performance of GeneXpert MTB/RIF in sputum samples from Pakistani patients with cavitary TB, using mycobacterial culture as the gold standard and comparing it to sputum smear microscopy. Methods: In this cross-sectional study conducted at a tertiary hospital in Rawalpindi, 187 HIV-negative adults (18–60 years) with cavitary pulmonary TB were enrolled. Sputum samples were analyzed by smear microscopy, GeneXpert, and culture at baseline, 2, 5, and 6 months of therapy. Diagnostic accuracy indices (sensitivity, specificity, PPV, NPV) were compared with culture results. Results: Among 187 patients (mean age 44.1 ± 17.1 years; 93.6% female), 32% had baseline culture-confirmed TB. GeneXpert detected 91.7% of culture-positive cases versus 28.3% by smear. After 2 months, 43.3% remained culture-positive, while GeneXpert and smear positivity were 35.3% and 32.6%, respectively. All patients achieved culture negativity by treatment completion; however, GeneXpert and smear remained positive in 49.2% and 41.7% due to non-viable bacilli. Conclusion: GeneXpert MTB/RIF demonstrated superior sensitivity to smear microscopy in detecting cavitary TB and monitoring therapeutic response, but showed reduced specificity post-treatment due to residual DNA. Combining GeneXpert with culture improves reliability for therapy monitoring and outcome prediction. Keywords: Tuberculosis, Mycobacterium tuberculosis; Polymerase Chain Reaction; Sputum; Sensitivity and Specificity; Treatment Outcome